The Concept of the Self in Come Walk with Me: A Memoir by Beatrice Mosionier - Rzepa, Agnieszka (Studia Anglica Posnaniensia, 2016)
Beatrice (Culleton) Mosionier is a Canadian Métis writer, whose first strongly autobiographical novel In Search of April Raintree (1983) has been recognized as a classic of contemporary Native Canadian literatures. Her memoir, Come Walk with Me (2009), describes her life story from 1949 till 1987, covering also the period between 1987 and 2001 in a brief epilogue. In the memoir, Mosionier uses fragments of the transcript of an interview conducted with her mother in 1984 by Alanis Obomsawin to preface the three parts of her book. Apart from constructing the two lives as parallel and in dialogue with one another, Mosionier frames and dialogises her story also through references to the process of writing, publication and the success of her novel; and reaches out to readers to induce them to “walk” with her. The aim of the present article is to examine the narrative presentation of the process of self-discovery focusing in particular on the relational aspects of the life story. Mosionier’s memoir demonstrates her growing into the realisation of the fact that her identity is relational-she recognizes herself as part of a larger ethnic and social group, and later also as shaped by familial relations. While depicting “the self [that] is dynamic, changing, and plural” (Eakin 1999: 98), she conceptualises it in reference to what she believes to be an essentially static core identity, and as “channelled” through a life that largely follows a predetermined pattern.